Neonicotinoids in global agriculture: evidence for a new pesticide treadmill? - Bakker, Lieneke; van der Werf, Wopke; Tittonell, Pablo; Wyckhuys, Kris A. G.; Bianchi, Felix J. J. A. (Ecology and society, 2020)
Overreliance on synthetic insecticides in global agriculture is the outcome of a "pesticide treadmill," in which insecticide-induced pest resistance development and the depletion of beneficial insect populations aggravate farmers' pesticide dependencies. Examples of the pesticide treadmill have been witnessed repeatedly over the past seven decades, prompting the question whether the rapid uptake and usage patterns of neonicotinoid insecticides and their associated environmental impact are in accordance with this recurrent phenomenon. We hypothesize a conceptual framework in which treadmills are enforced by enabling or disabling drivers within four domains: pest management decisions at the farm level, characteristics of farming landscapes, science and technology, and societal demands. These drivers then tend to create a self-enforcing pesticide "lock-in." We then analyze several post-1950s historical case studies with reference to this framework, e.g., those involving sprays of the highly hazardous DDT and methyl-parathion, in which the pesticide treadmill was initiated, sustained, and broken, and compare this with current patterns in neonicotinoid use. Historical case studies further illustrate how treadmills occur in three phases in which (i) a limited number of insecticides are routinely used, (ii) resistance development of pests results in the increased crop injury, prompting increased frequency of applications with a wider range of products, (iii) breaking out of the pesticide "lock-in" by policy change and adoption of alternative technologies that lowered chemical inputs and improved agro-ecosystem functioning. The analysis shows similarities as well as differences between neonicotinoid usage patterns and historic pesticide treadmills, and provides guidance on how to effectively avoid or dismantle pesticide treadmills in global agriculture.